How corporate marketing strategy can leverage UN 2030 Sustainable Development Goals - Mendes, A. C.; Pereira, L. F.; Dias, Á.; Silva, R. V. da.; Teixeira, N. (World Review of Science, Technology and Sustainable Development, 2024)
Sustainability is highly valued nowadays due to the surroundings of social and environmental pressure and concern over the past few years, such as the United Nations suggested goals to make prosperity beneficial to all. The main objective of this research is to understand how the sustainable development goals (SDGs) can affect the marketing strategy of the companies, considering that theres a lack of literature between these two fields of knowledge. This research develops a qualitative approach using interviews from marketing directors to respond about business ways of marketing strategies used to enhance sustainability. In findings, it is verified a crucial marketing view with product related matters as solutions, external pressure and communication as a relevant tool. Another interesting finding is that consumption, processes and others in creating sustainable value for everyone are a current challenge.